Hubungan antara Adversity Quotient dan Dukungan Sosial terhadap Stres Akademik pada Mahasiswa yang Bekerja di Universitas Muhammadiyah Sidoarjo: The Relationship Between Adversity Quotient and Social Support on Academic Stress Among Working Students at Universitas Muhammadiyah Sidoarjo - Evi Noor Khikmah Apriliani; Ghozali Rusyid Affandi (Universitas Muhammadiyah Sidoarjo, 2025)
This study addresses the growing concern of academic stress among university students in higher education settings. General Background: Academic stress has become a prominent psychological issue affecting students’ well-being and academic functioning. Specific Background: Psychological resilience factors such as adversity quotient and external resources such as social support are frequently associated with students’ capacity to manage academic demands. Knowledge Gap: However, limited empirical studies have simultaneously examined the relationship between adversity quotient and social support in explaining academic stress within the same analytical model. Aims: This research aims to analyze the relationship between adversity quotient, social support, and academic stress among university students. Results: The findings indicate a significant relationship between adversity quotient and academic stress, as well as between social support and academic stress. Simultaneously, adversity quotient and social support demonstrate a significant association with academic stress levels. Novelty: The study provides an integrated empirical examination of internal resilience and external social resources in relation to academic stress within a single quantitative framework. Implications: These findings highlight the importance of strengthening students’ resilience capacity and social support systems to address academic stress in higher education contexts. Keywords: Adversity Quotient, Social Support, Academic Stress, University Students, Psychological Resilience Key Findings Highlights: Higher resilience capacity is associated with lower levels of study-related tension. External relational resources show significant association with psychological pressure in academic settings. Internal and external factors jointly demonstrate statistical relevance in predicting students’ stress levels.